EFEKTIFITAS GAME EDUKASI UNTUK MENINGKATKAN KEMAMPUAN PENJUMLAJAN BAGI ANAK KESULITAN BELAJAR DI MIN KOTO LUAR, KECAMATAN PAUH - Fitriyeni, Yarmis Hasan, Tarmansyah (Universitas Negeri Padang, 2013)
This research is motivated by the child's learning disabilities who can not do the sums 1-20. From which researchers gave test, the child can not do the sums 1-20. This study aims to prove the effectiveness of educational games for kids summation improve learning disabilities. Type of research is the Single Subject Research, with ABA design and data analysis techniques using visual analysis chart. Measurement variables using a percentage of the number of questions answered correctly. Observations were made in three sessions, the first session before being given intervention baseline (A1) performed seven times of observation. In this session children upon ability children were in the range of 15%, 20%, and 10%. Second, the intervention sessions (B) through a given educational game nine times, observations, suggests that increasing a child's ability to be in the range of 25%, 30%, 60%, 75%, 90%, and up to 100%. Third, baseline sessions after the intervention no longer given (A2) are given for seven observations and answer questions upon ability summation children were in the range of 65%, 80%, 95%, and 100%. From the results of this study indicate that effective educational games to enhance the ability of the sum of numbers for child learning disabilities in MON Koto Affairs, District Pauh. So that educational games can be used as one solution to help improve the child’s ability to sum numbers learning disabilities.